Office of Clinical Pharmacology Science Day: A Forum to Stimulate Innovation in Clinical Pharmacology. Issue 6 (12th February 2013) - Owen, R P; Jain, L; Zhang, L; Zineh, I
<x xml:space="preserve">Abstract</x> The Office of Clinical Pharmacology (OCP) of the US Food and Drug Administration (FDA) has hosted an office‐wide event called Science Day (SD) since 1999. SD 2012 included presentations on physiologically based pharmacokinetic models, exposure–response analyses, and other research projects. SD provides a forum for showcasing clinical pharmacology (CP) research within the OCP and provides an opportunity for professional development. This article discusses the evolution of Science Day and then focuses on SD 2012 as an example platform for promotion of regulatory research. Clinical Pharmacology & Therapeutics (2013); 93 6, 471–473. doi:10.1038/clpt.2013.33